Decreased collagen type i is associated with increased metalloproteinase-2 activity and protein expression of leptin in the myocardium of obese rats - da Silva-Bertani, Danielle Cristina Tomaz [UNESP]; Vileigas, Danielle Fernandes [UNESP]; Mota, Gustavo Augusto Ferreira [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; De Tomasi, Loreta Casquel [UNESP]; de Campos, Dijon Henrique Salomé [UNESP]; de Deus, Adriana Fernandes [UNESP]; Freire, Paula Paccielli [UNESP]; Alves, Carlos Augusto Barnabe [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Sociedade Brasileira de Cardiologia, 2020)
Background: Obesity is a risk factor for medical complications, including the cardiovascular system. There is limited information on collagen in the heart in obesity. Our previous study showed decreased protein levels of myocardial collagen type I in obese rats fed a high-fat diet for 34 weeks. However, the mechanisms responsible for low levels are not fully elucidated. Objective: The purpose of this study was to test the hypothesis that the reduction in collagen type I is associated with increased metalloproteinase-2 (MMP-2) activity, which is linked to elevated leptin in the myocardium of obese rats. Methods: Thirty-day-old male Wistar rats were randomized into two groups, control (standard diet) and obese (high-fat diet), and fed for 34 weeks. The general animal characteristics and metabolic and endocrine profiles were evaluated. Myocardial protein expressions of collagen I, leptin, tissue inhibitors of metalloproteinases (TIMP), and MMP-2 activity were assessed. Pearson correlation was employed to determine the associations between variables. The level of significance was 5%. Results: The obese animals had increased adiposity index compared to control. Comorbidities such as glucose intolerance, hyperinsulinemia, insulin resistance, hyperleptinemia, and hypertension were observed in obese rats. Obesity reduced collagen I, TIMP-1, and TIMP-2, and it increased leptin and MMP-2 in the myocardium. There was a negative correlation between collagen I and MMP-2 and a positive correlation between leptin and MMP-2. Conclusion: The hypothesis was confirmed; the reduction in collagen type I is associated with increased MMP-2 activity and leptin expression in the myocardium of obese rats. (Arq Bras Cardiol. 2020; 115(1):61-70).
A redução do colágeno tipo i está associada ao aumento da atividade da metaloproteinase-2 e da expressão proteica de leptina no miocárdio de ratos obesos
Keywords: Adiposity; Cardiovascular Diseases/physiopathology; Collagen Type 1; Leptin; Metaloproteinase-2; Obesity; Rats; Tissue Inhibitor of Metalloproteinases